2016
DOI: 10.1108/ilds-01-2016-0001
|View full text |Cite
|
Sign up to set email alerts
|

E-lending in digital libraries: a systematic review

Abstract: Purpose The purpose of this paper is to systematically review e-lending research studies in the digital library domain to identify their subjects, existing research gap and their research methods. Design/methodology/approach This is a systematic review. Through several stages of searching in related databases, 30 research works including journal and conference research papers, theses and dissertations, research and technical reports were identified and reviewed based on the guidelines of systematic review pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The e-lending has been an object of study for many researchers over recent years. Alipour-Hafezi and Khedmatgozar (2016) have identified that scholars predominantly focused on the topic of e-book specification, creation and software, as well as the perspectives of librarians and users. Another vital area of investigation is e-lending in the context of interlibrary loans and copyright issues in general.…”
Section: E-lending Models and Ownershipmentioning
confidence: 99%
“…The e-lending has been an object of study for many researchers over recent years. Alipour-Hafezi and Khedmatgozar (2016) have identified that scholars predominantly focused on the topic of e-book specification, creation and software, as well as the perspectives of librarians and users. Another vital area of investigation is e-lending in the context of interlibrary loans and copyright issues in general.…”
Section: E-lending Models and Ownershipmentioning
confidence: 99%
“…With the growth of e-book collections, their lending is also increasing, and so also the literature on this topic. Alipour-Hafezi and Khedmatgozar 57 presented systematic review of literature on e-lending and identified gaps in research on this topic.…”
Section: Management and Ill Of E-booksmentioning
confidence: 99%
“…The borrowing e-book for users will increase in the future, according to the classifications of electronic borrowing [4]. E-books are borrowed and used effectively.…”
Section: Introductionmentioning
confidence: 99%